2009
DOI: 10.1080/02841860903104137
|View full text |Cite
|
Sign up to set email alerts
|

Does enhanced information at cancer genetic counseling improve counselees’ knowledge, risk perception, satisfaction and negotiation of information to at-risk relatives? – a randomized study

Abstract: (2009) Does enhanced information at cancer genetic counseling improve counselees' knowledge, risk perception, satisfaction and negotiation of information to at-risk relatives? -a randomized study, Acta Oncologica, 48:7, 999-1009,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(64 citation statements)
references
References 27 publications
2
62
0
Order By: Relevance
“…This supports the findings of a previous study on accuracy of recall of patients with cancer and their relatives, which found that information about cancer risk was the least accurately recalled. 25 However, in a study of first-degree relatives undergoing predictive testing for BRCA1/2 mutations, higher levels of Accuracy of information about a BRCA1/2 mutation C Jacobs et al accuracy about hereditary cancer than inheritance were reported. 16 For the cancer patients in this study, general genetics information would have been addressed during pre-test genetic counselling, whereas specific hereditary cancer information may not have been discussed in detail prior to learning the genetic test result.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This supports the findings of a previous study on accuracy of recall of patients with cancer and their relatives, which found that information about cancer risk was the least accurately recalled. 25 However, in a study of first-degree relatives undergoing predictive testing for BRCA1/2 mutations, higher levels of Accuracy of information about a BRCA1/2 mutation C Jacobs et al accuracy about hereditary cancer than inheritance were reported. 16 For the cancer patients in this study, general genetics information would have been addressed during pre-test genetic counselling, whereas specific hereditary cancer information may not have been discussed in detail prior to learning the genetic test result.…”
Section: Discussionmentioning
confidence: 99%
“…The mean number of information statements communicated to patients was 21 (range [16][17][18][19][20][21][22][23][24][25][26].…”
Section: Participantsmentioning
confidence: 99%
“…One of the roles of a genetic counsellor is to help individuals and families understand complex genetic information and share it with the family (Genetic Alliance 2009). Those receiving additional information are more satisfied, especially if this leads to better understanding (Roshanai et al 2009). This may indicate that the opportunity for a follow-up session to reinforce and expand on the information given could be valued and useful to counselees.…”
Section: Discussionmentioning
confidence: 99%
“…This theme comprises nine papers with studies focussing on professionals' practice [35][36][37] and specific interventions to assist consultands in the communication of information to at-risk relatives. [38][39][40][41][42][43] Features of practice included psychoeducational guidance and information aids that were used as adjuncts to clinical practice.…”
Section: Studies Included In Quantitative Synthesismentioning
confidence: 99%